PERANCANGAN BUKU POP-UP “MENGENAL BUDAYA BUGIS” SEBAGAI MEDIA PEMBELAJARAN UNTUK ANAK USIA 7-12 TAHUN - Andi Fauziyah Hijrina; Muhammad Zia Ulhaq (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2026)
In the modern era, the preservation of local cultural values faces significant challenges, particularly among Generation Alpha. The lack of engaging and communicative educational media for children aged 7 to 12 contributes to the decline in cultural awareness. This study aims to design and develop an interactive pop-up book as a cultural learning medium introducing Bugis ethnic traditions through engaging three-dimensional visuals. The development process employed a qualitative approach with the Four-D model (Define, Design, Develop). The results indicate that the pop-up book effectively serves as an innovative learning tool that enhances children’s interest in local culture and supports the transmission of cultural values. This book is expected to serve as a model for local wisdom-based educational media in Indonesia's cultural education curricula.